2012
DOI: 10.1212/wnl.0b013e31826043a9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sites of new hemorrhage with amyloid imaging in cerebral amyloid angiopathy

Abstract: Objective: We aimed to determine whether amyloid imaging can help predict the location and number of future hemorrhages in cerebral amyloid angiopathy (CAA). Methods:We performed a longitudinal cohort study of 11 patients with CAA without dementia who underwent serial brain MRIs after baseline amyloid imaging with Pittsburgh compound B (PiB). Mean distribution volume ratio (DVR) of PiB was determined at the sites of new micro/ macrobleeds identified on follow-up MRI and compared with PiB retention at "simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 25 publications
2
95
0
3
Order By: Relevance
“…Pittsburg compound B is a radiologic marker of amyloid plaques used to quantify cerebral amyloid load in vivo. [49][50][51] Results showed a positive correlation between WMH volume and cortical PiB uptake in patients with CAA, but not in patients with Alzheimer's disease or healthy elderly controls, 5 suggesting a direct relationship between subcortical WMH and cortical CAA pathology. Furthermore, two studies found that the distribution of WMH in patients with CAA is predominantly posterior, in line with the predominant posterior distribution of CAArelated vascular amyloid.…”
Section: White-matter Hyperintensitiesmentioning
confidence: 95%
“…Pittsburg compound B is a radiologic marker of amyloid plaques used to quantify cerebral amyloid load in vivo. [49][50][51] Results showed a positive correlation between WMH volume and cortical PiB uptake in patients with CAA, but not in patients with Alzheimer's disease or healthy elderly controls, 5 suggesting a direct relationship between subcortical WMH and cortical CAA pathology. Furthermore, two studies found that the distribution of WMH in patients with CAA is predominantly posterior, in line with the predominant posterior distribution of CAArelated vascular amyloid.…”
Section: White-matter Hyperintensitiesmentioning
confidence: 95%
“…6 One of the exciting advances in CAA research has been the demonstration of the ability of Pittsburgh compound B (PiB), originally designed to detect plaque amyloid in Alzheimer disease (AD), to label vascular amyloid as well. [7][8][9][10] This PET tracer was shown to bind vascular amyloid by radiologic-pathologic correlation in both the common sporadic form of CAA and Iowa-type hereditary CAA, a form of the disorder with little or no plaque deposits of fibrillar Ab. 11,12 Amyloid imaging using PiB-PET has already made important contributions to our understanding of CAA-related hemorrhagic and ischemic disease mechanisms, 2,7,8,13,14 such as prediction of future hemorrhages.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…1,3,29 On the other hand, several attempts using amyloid imaging, such as 11 C-Pittsburgh compound B positron emission tomography ( 11 C-PiB PET), have been made to detect CAA as an underlying disease in several pathological conditions such as dementia, cortical SAH, and cerebral angitis. [30][31][32][33][34] A positive relationship between local amyloid burden and a future risk for hemorrhage has been suggested based on the result of a longitudinal cohort study with 11 C-PiB PET and MRI. 31 However, the presence of vascular amyloid in the tissue sample is not perfectly specific for CAA-ICH because elderly people may incidentally present with asymptomatic vascular amyloid deposition.…”
Section: Factors That Influence the Detection Of Caa Pathologymentioning
confidence: 99%
“…[30][31][32][33][34] A positive relationship between local amyloid burden and a future risk for hemorrhage has been suggested based on the result of a longitudinal cohort study with 11 C-PiB PET and MRI. 31 However, the presence of vascular amyloid in the tissue sample is not perfectly specific for CAA-ICH because elderly people may incidentally present with asymptomatic vascular amyloid deposition. 3,4,11 For more definitive diagnosis of CAA-ICH, ruptured amyloid-laden blood vessels adjacent to the hematoma should be identified in postmortem study.…”
Section: Factors That Influence the Detection Of Caa Pathologymentioning
confidence: 99%